Response surface methodology for optimizing adsorption process parameters for tadalafil removal by raw eggshell - Halici, Zeynep; Demirhan, Elcin (SPRINGER HEIDELBERG, 2025)
Excessive discharge of pharmaceutical wastes into the surface water causes harmful effect on environment, so its removal has aroused much attention in recent years. This study investigated the potential of raw eggshell as a low cost adsorbent on the removal of tadalafil by adsorption experiments. Characterization of adsorbent was investigated using Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscope (SEM) and X-ray diffraction (XRD). To comprehensively evaluate the independent and interacting effects of several process factors, such as pH, temperature, and amount of adsorbent, Box-Behnken design was used. According to results of variance analysis (ANOVA) it was concluded that the second-order model had strong statistical relevance and was characterized by a high coefficient of determination (R2) value. It was clear from the experimental results that as the pH level and adsorbent amount were raised, so was the removal efficiency. At pH 5, 25 degrees C, and 7.5 g/100 mL of adsorbent, the greatest removal efficiency of 72.9% was attained. Furthermore, the analysis of equilibrium data showed that, in comparison to the Langmuir isotherm model, the Freundlich isotherm model offered a better fit for dye removal. Furthermore, the adsorption kinetic was also evaluated and it was obtained the adsorption followed by pseudo second order model for the tadalafil removal onto eggshell.
Keywords: Pharmaceutical; Tadalafil; Adsorption; Low-cost adsorbent; Box-Behnken design; Isotherm; Kinetic; WASTE-WATER TREATMENT; AQUEOUS-SOLUTION; PROCESS OPTIMIZATION; DYE REMOVAL; PHARMACEUTICALS; DICLOFENAC; ELECTROCOAGULATION; KINETICS; BED; Energy & Fuels; Engineering